Menstrual Hygiene: Knowledge and Practice Among Adolescent Girls of Rural Kheda District - Prajapati, Dhara J; Shah, Janmesh P; Kedia, Geeta (National Journal of Community Medicine, 2015)
Background: Menarche is not just a physiological phenomenon but it is a psychological, social as well as behavioral transition for an adolescent girl from girlhood to womanhood. Menstrual hygiene is most important, still neglected area of concern. Objective of study was to find out menstrual pattern, knowledge and practice among adolescent girls. Method: A cross sectional study was undertaken in a rural area of Kheda district. Randomly selected 200 adolescent girls were inter- viewed using predesigned pretested questionnaire. Results: It was evident that 47.5% participants were aware about menstruation before their menarche and the most important sources of information were mothers in 54% girls.10.5% respond- ents used only sanitary napkin during menstruation. 77% changed absorbent 1 to 2 times a day. Conclusion: This study has highlighted the need of adolescent girls to have accurate and adequate information about menstruation.